Exploring Corporate Strategic Management and Global Expansion on the Case study of Samsung Electronics - Haroun, Ibrahim Mussa (Archives of Business Research, 2016)
Basically, to offset any potential future concerns the organizations must be embedded with sustainable strategies which could restore the organization’s reputation as well as competitive advantage. In the 21st century however, many organizations have grown hot with the ideology and so working hard to formulate strategies which could potentially keep them stay in the business and achieve their intended goals and objectives. Perhaps even more significantly, to achieve their strategic move, many of these organizations have opted to go global. This piece of research however, intends to investigate on the concept of “Assembling the Global Enterprise” whereby the report will be produced based on the “Samsung Electronics” where the adaptation of context, theories, models and tools containing within the strategic management become and appears to be the central part of the theme.